Evaluation of daylighting performance in existing student residential building with internal partition / Khairul Azmi Mohamed, Asmat Ismail and Nur Azfahani Ahmad - Mohamed, Khairul Azmi; Ismail, Asmat; Ahmad, Nur Azfahani (2019)
The Polytechnic Ungku Omar residential college building was designed with an internal partition to accommodate six (6) people per room. However, the installation of an internal partition has resulted in lowering the illumination level inside the building. While the rooms are designed with internal partition, the layout of the internal partition may influence the indoor daylighting distribution. Therefore, this study is intended to evaluate the impacts of several internal partition layout on indoor daylighting performance in residential college rooms. The field measurement was conducted in a typical student residential room under a tropical sky to validate the result of the simulation under Climate Based Daylight Modelling (CBDM). Then several options of internal partition were simulated using DIVA for Rhino to suggest the possible partition layout that is effective to overcome low daylighting level in student residential rooms. The finding indicates that by changing the internal partition layout in a student residential room in the tropics have a robust impact on daylight sufficiency. It is revealed that the highest annual daylight sufficiency values belong to those internal partitions oriented perpendicular to the window. These improvements could provide a comfortable, productive and healthy environment for occupants as well as savings in annual energy consumption.